Dictionary on Comprehensive Security in Indonesia : Acronyms and Abbreviations, Kamus Keamanan Komprehensif Indonesia : Akronim dan Singkatan - Wandelt, Ingo (Friedrich Ebert Stiftung (FES) Indonesia Office, 2009)
220 p. : Ill.; 21 cm